Acetyl-CoA carboxylase-1/2 blockade locks dendritic cells in the semimature state associated with FA deprivation by favoring FAO. Issue 3 (24th May 2021) - Nguyen-Phuong, Thuy; Chung, Hyunwoo; Jang, Jiyun; Kim, Jung-Sik; Park, Chung-Gyu
Abstract: Immunometabolism is rising as an intriguing topic that reveals the connection between immune cell function and metabolic processes. Especially, fatty acid metabolism plays an essential role in the dendritic cells (DCs) during the differentiation and maturation period. We questioned whether regulation of acetyl-CoA carboxylases 1 and 2-(ACC1/2), the core enzymes of fatty acid synthesis (FAS), would control DC function. Here, we report that blocking ACC1/2 to prevent FAS during DC maturation switched their cellular metabolism into fatty acid oxidation to fuel oxidative phosphorylation. This action turned DCs to utilize exogenous fatty acids to sustain their basal energy demand and maintain a stable cellular respiration rate. Coincidentally, under the ACC1/2 inhibitor treatment, LPS-treated DCs exhibited a semimaturation phenotype with a maturation-resistance feature, with decreased expression of costimulatory molecules including CD86 and CD40, along with the reduction of IL-12 and IL-6. The migratory capability of DCs has been known to relate to the glycolysis pathway, and here we showed that the ACC1/2 blockade did not affect the expression of CCR7 and DC migration. Furthermore, we found that under the ACC1/2 blocking condition, DCs pulsed with OVA failed to activate OVA-specific CD4+ T cell proliferation even though their antigen uptake capacity was intact. Together, our data suggest ACC1/2 as a promising target to control DC fate. Graphical Abstract: Blocking acetyl-CoA carboxylases 1 and 2-(ACC1/2) deprives of fatty acids, through a fatty acid oxidation pathway, in activated dendritic cells (DC), inducing a semi-mature DC phenotype with a maturation-resistant feature.